FUNGSI TARI MANIAMAS DALAM UPACARA ADAT NYOBENG PADA SUKU DAYAK BIDAYUH DESA SEBUJIT KABUPATEN BENGKAYANG - Riri, Linovia; Ismunandar, Ismunandar; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research is conducted with background that society lack of interest toward traditional dance function. In Nyobeng ceremony, Bidayuh Dayaknesse has several sacred dances which performanced. In the first day of Nyobeng ceremony, a dance called Maniamas is dance where the dancers circling a certain house, the cube house, while Maniamas instrumental is played. The purposes of this research are to review the function of Maniamas dance thoroughly and to learn every steps of preparation before the performance.The metodology of this research is descriptive-equalitative with anthropology approach. The source is Gunawan whom familiar with Maniamas ritual in Nyobeng ceremony in Sebujit village. The data of analysis are interview and documents.The result of this study was to explain that Maniamas dance was a ritual dance characterised by its place, dancers, date, offering, purposes, and costume which gave a sacred vibe. Maniamas danced with purposes to welcome the guests and to thank God who gave lifes, who delivered human from evil, also as a mediation to summon the ancestors spirit which kept the Nyobeng ritual safe. Nyobeng is a ceremony which cleanse the sacred items like skeleton from â€œmengayauâ€ done by elders in past time. Nyobeng has 11 steps to follow and it is held in seven consecutive days. This study contributed learning materials for eleventh grade students in CD form.Â Keywords: ritual, Nyobeng, Maniamas dance. Â